Considered Interest in Criminalizing Assault on Public Facilities - Kadhum, Esraa; Abood, Samer (Journal of Legal Sciences, 2023)
Public utilities are the most important institutions at the present time, because of their great importance in providing daily services to citizens to meet their needs, and thus help the state to develop and progress in various social, economic and even security fields, and they also have a major role in creating an environment filled with stability and good life. Due to the great importance of public utilities, the hand of the legislator extended to protecting and regulating them in many legal texts, so he singled out many texts for them, whether in regulatory or even penal laws, and because penal texts are the most important legal texts because of their great role in protection, as well as their connection to the rights and freedoms of individuals. Therefore, it became necessary to research these texts and clarify the interest in their legislation, because the philosophy of the legislator in penal texts is their interest. In order to determine the interest considered in crimes committed against public utilities, we divided the research into two chapter the first to show the concept of interest and public utilities. As for the second topic, we explained in it the interest that is the subject of criminal protection for public utilities.